Accreting coral reefs in a highly urbanized environment - Januchowski-Hartley, Fraser A.; Bauman, Andrew G.; Morgan, Kyle M.; Seah, Jovena C. L.; Huang, Danwei; Todd, Peter A. (Coral reefs, 2020)
Globally, many coral reefs have fallen into negative carbonate budget states, where biological erosion exceeds carbonate production. The compounding effects of urbanization and climate change have caused reductions in coral cover and shifts in community composition that may limit the ability of reefs to maintain rates of vertical accretion in line with rising sea levels. Here we report on coral reef carbonate budget surveys across seven coral reefs in Singapore, which persist under chronic turbidity and in highly disturbed environmental conditions, with less than 20% light penetration to 2 m depth. Results show that mean net carbonate budgets across Singapore’s reefs were relatively low, at 0.63 ± 0.27 kg CaCO 3 m −2 yr −1 (mean ± 1 SE) with a range from − 1.56 to 1.97, compared with the mean carbonate budgets across the Indo-Pacific of 1.4 ± 0.15 kg CaCO 3 m −2 yr −1 , and isolated Indian Ocean reefs pre-2016 bleaching (~ 3.7 kg CaCO 3 m −2 yr −1 ). Of the seven reefs surveyed, only one reef had a net negative, or erosional budget, due to near total loss of coral cover (< 5% remaining coral). Mean gross carbonate production on Singapore’s reefs was dominated by stress-tolerant and generalist species, with low-profile morphologies, and was ~ 3 kg m −2 yr −1 lower than on reefs with equivalent coral cover elsewhere in the Indo-Pacific. While overall these reefs are maintaining and adding carbonate structure, their mean vertical accretion potential is below both current rates of sea level rise (1993–2010), and future predictions under RCP 4.5 and RCP 8.5 scenarios. This is likely to result in an increase of 0.2–0.6 m of water above Singapore’s reefs in the next 80 yr, further narrowing the depth range over which these reefs can persist.